Økonomisk politik – nødvendighed, konsensus eller ideologi? - Andersen, Torben M. (Politik, 2013)
Policy discussions are centered on economic policies and reforms. e driver in this process is the challenge of ensuring the nancial viability of an extended welfare state due to demographic changes and reinforced by the economic crisis. Economic policies may appear defensive solely enforced by necessities. However, a base for maintaining an extended welfare state has been ensured, and in comparative perspective this re ects a clear ideological choice.